Experimental Research on Impinging Slot Jet on a Concave Surface - Effects of Impinging Height and Reynolds Number - Hoang, Thi Kim Dung (Old Journal, 2017)
Experimental research of single slot impinging jet upon a concave surface were conducted by classical Particle Image Velocimetry (PIV) and infrared thermography. Main parameters of this research were nozzle exit Reynolds number $(Re_{b}=1400-6400)$, dimensionless impinging height $(H/b=3-7)$, relative curvature of wall $(D_{c}/b=5)$ and little dissymmetric outlet flow $(e/b=0.8)$. Results indicated that impinging jet oscillated at three semi-stable different point at high impinging height while it stabilized at a position at small impinging height. Therefore, oscillation of impinging jet generated a uniform heat transfer at high impinging height while stabilized impinging jet caused an asymmetric heat transfer at low impinging height.